Recurrent Aphthous Ulceration Prevalence And The Factors Associated with It Among Dentistry Students /Tikrit University: Prevalensi Ulserasi Aftosa Berulang Dan Faktor-Faktor Yang Berhubungan Dengannya Di Kalangan Mahasiswa Kedokteran Gigi / Universitas Tikrit - Aswad , Fatima Ghazi (Universitas Muhammadiyah Sidoarjo, 2024)
Background: The most prevalent condition affecting the mucosa of the oral cavity is recurrent aphthous stomatitis (RAS), also called canker sores. Individuals with RAS cannot avoid it, in contrast to patient with periodontal disorder and dental caries. The feature RAS clinical picture is identified by recurring bouts of painful ulcerations which appear either single or multiple in different site in the mouth that include lips, buccal mucosa, tongue, and soft palate in the mucosa that are not keratinized. Frequently appear spherical, unpleasant, and covered by a yellowish gray fibromembranous thin layer, with a read boundary. Despite the present of. numerous recommendations, there is still no exact treatment for recurrent phathous canker because the origin etiology is still controversial and its occurrence is affected by a variety of factor. Objectives: This study sought to evaluate the prevalence of recurrent apathies stomatitis and associated risk factors clinically . Method: This cross sectional study used as ample of 220 participants from the University of Tikrit's dental school. Every patient made an interview and as well as an oral cavity examination. During an interview Details were evaluated such as risk variables, using a distinct questionnaire that encompass characteristics of the study individual frequency of ulcer occurrence gender, age, class. Descriptive and inferential analyses and. association were included in the statistical study.X2 statistics were used to test relationships between the variables. Results: high prevalence of canker sores in female 64.3%. stress, diet and family history was the most frequently risk condition (82.6%) (79.1%) (69.8%, respectively). by patients, followed by diet and family history (79.1% and 69.8%, respectively). No statistical relation was found with trauma. Product of Tobacco using is related to aphthous development (p value less than 0.05). Conclusions: It was conducted that the prevalence of ulcer is high among dentistry student and the stress, diet and history of family are the most common risk condition. Highlights: Recurrent aphthous stomatitis causes painful oral ulcers with unclear etiology. Examined 220 dental students; analyzed risk factors via questionnaire and oral exams. High prevalence in females; stress, diet, and genetics are key risks. Keywords: Prevalence, Aphthous Stomatitis, Risk Factors